PENGARUH BRAND IMAGE TERHADAP PURCHASE INTENTION MELALUI E-TRUST (STUDI PADA CALON KONSUMEN ONLINE STORE HOODIEKU) - Imam Bahroni; Hanief Karsa Manggala (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2023)
In this day and age you can find many shops selling their products through internet media, one of the many products that are sold online is clothing or fashion products. Along with the rise of online stores circulating on the internet, potential consumers must be more confident in choosing products fashion, not all brands and online stores have a good reputation and are trusted, therefore to avoid a series of risks that can occur in online transactions, consumers will tend to seek as much information as possible about the brands and online stores they will choose before making a purchase. This study aims to determine the effect of Brand Image on Purchase Intentions through the online store of potential E-Trust Hoodieku customers. This research is a quantitative research using a descriptive and explanatory research design. The population taken in this study was the Instagram Official Store Hoodieku followers. The samples taken in this study were 205 respondents. The analysis technique uses descriptive statistical analysis and Partial Least Square (PLS) analysis. The results of the PLS test show that: (1) There is a positive and significant direct effect of Brand Image on E-Trust; (2) There is a positive and significant direct effect of E-Trust on Purchase Intentions; (3) There is a positive and significant indirect effect of Brand Image on Purchase Intention through E-Trust as a mediating variable.